Ultrafine particles altered gut microbial population and metabolic profiles in a sex-specific manner in an obese mouse model - Yang, Kundi (Sci Rep, 2021)
Emerging evidence has highlighted the connection between exposure to air pollution and the increased risk of obesity, metabolic syndrome, and comorbidities. Given the recent interest in studying the effects of ultrafine particle (UFP) on the health of obese individuals, this study examined the effects of gastrointestinal UFP exposure on gut microbial composition and metabolic function using an in vivo murine model of obesity in both sexes. UFPs generated from light-duty diesel engine combustion of petrodiesel (B0) and a petrodiesel/biodiesel fuel blend (80:20 v/v, B20) were administered orally. Multi-omics approaches, including liquid chromatography–mass spectrometry (LC–MS) based targeted metabolomics and 16S rRNA gene sequence analysis, semi-quantitatively compared the effects of 10-day UFP exposures on obese C57B6 mouse gut microbial population, changes in diversity and community function compared to a phosphate buffer solution (PBS) control group. Our results show that sex-specific differences in the gut microbial population in response to UFP exposure can be observed, as UFPs appear to have a differential impact on several bacterial families in males and females. Meanwhile, the alteration of seventy-five metabolites from the gut microbial metabolome varied significantly (ANOVA p < 0.05) across the PBS control, B0, and B20 groups. Multivariate analyses revealed that the fuel-type specific disruption to the microbial metabolome was observed in both sexes, with stronger disruptive effects found in females in comparison to male obese mice. Metabolic signatures of bacterial cellular oxidative stress, such as the decreased concentration of nucleotides and lipids and increased concentrations of carbohydrate, energy, and vitamin metabolites were detected. Furthermore, blood metabolites from the obese mice were differentially affected by the fuel types used to generate the UFPs (B0 vs. B20).